2020
DOI: 10.1038/s41598-020-58638-8
|View full text |Cite
|
Sign up to set email alerts
|

Fine-grained climate velocities reveal vulnerability of protected areas to climate change

Abstract: climate change velocity is an increasingly used metric to assess the broad-scale climatic exposure and climate change induced risks to terrestrial and marine ecosystems. However, the utility of this metric in conservation planning can be enhanced by determining the velocities of multiple climatic drivers in real protected area (pA) networks on ecologically relevant scales. Here we investigate the velocities of three key bioclimatic variables across a nationwide reserve network, and the consequences of includin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 26 publications
(33 citation statements)
references
References 48 publications
1
32
0
Order By: Relevance
“…The post-2020 biodiversity protection agenda [105] will focus on expanding the existing PAs [106,107]. Many PAs are exposed to spillover effects due to land-cover change [108] and are facing increased climate-change-based risks [109]. It would thus be prudent to aim the conservation efforts at areas with overlaps among PAs and climatic refugia, simultaneously characterised by high diversity and EDGE scores (including the taxa with the highest EDGE scores).…”
Section: Conservation and Management Implicationsmentioning
confidence: 99%
“…The post-2020 biodiversity protection agenda [105] will focus on expanding the existing PAs [106,107]. Many PAs are exposed to spillover effects due to land-cover change [108] and are facing increased climate-change-based risks [109]. It would thus be prudent to aim the conservation efforts at areas with overlaps among PAs and climatic refugia, simultaneously characterised by high diversity and EDGE scores (including the taxa with the highest EDGE scores).…”
Section: Conservation and Management Implicationsmentioning
confidence: 99%
“…An expansion of the existing protected areas [ 136 , 137 ], as is included in the post-2020 biodiversity protection agenda [ 11 ] could potentially triple the species’ range under protection, as well as that of phylogenetic/functional units [ 138 ]. Many protected areas are also facing increased climate change based risks [ 139 ]. In the era of rapid biodiversity decline [ 140 ], it is necessary to investigate if different facets of biodiversity are included in existing protected areas [ 141 ] and to identify new areas of high evolutionary and conservation value.…”
Section: Discussionmentioning
confidence: 99%
“…The ability of Habitats Directive species to achieve and retain a favourable conservation status can be challenging in an era of accelerating global changes. Modelling studies have suggested that many Habitats Directive species populations will be negatively affected by climate change (Araujo et al, 2011;Normand et al, 2007), and notable future alterations in climate conditions in N2000 areas may occur (Heikkinen et al, 2020;Nila and Hossain, 2019), introducing turnovers in species communities (Thuiller et al, 2014;Virkkala and Lehikoinen, 2017). Importantly, negative impacts of climate change may be boosted by interactions with adverse land use (Hülber et al, 2020;Jetz et al, 2007;Oliver and Morecroft, 2014;Segan et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…However, effective incorporation of climate change-land use adaptation strategies in the national-scale management of at-risk species, including Habitats Directive species, would benefit from further attention on three issues: (i) relevant spatial scale of vulnerability assessments, (ii) vulnerability differences between different local populations, and (iii) species-specific impacts of land use, including both negative and positive impacts. Most vulnerability studies have been conducted at a rather coarse scale and overlook local changes in the topoclimate (Heikkinen et al, 2020;Rapacciuolo et al, 2014). Ideally, scrutinizing fine-resolution climatic and land-use risks may help in detecting occurrences of the vulnerable species and directing conservation and management resources to sites providing maximal potential benefits (Crossman et al, 2012;Rannow et al, 2014;Suggitt et al, 2018), but experience on this is sparse.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation